How to Create a Web3 Startup A Guide for Tomorrow's Breakout Companies - Taulli, Tom. (Berkeley, CA : Apress : Imprint: Apress, 2022)
Web3 is the next evolution for the World Wide Web based on Blockchain technology. This book will equip entrepreneurs with the best preparation for the megatrend of Web3 by reviewing its core concepts such as DAOs, tokens, dApps, and Ethereum. With Web2, much of the valuable data and wealth has been concentrated with a handful of mega tech operators like Apple, Facebook, Google and Amazon. This has made it difficult for startups to get an edge. It has also meant that users have had little choice but to give up their value data for free. Web3 aims to upend this model using a decentralized approach that is on the blockchain and crypto. This allows for users to become stakeholders in the ecosystem. Along with exploring core concepts of Web3 like DAOs, tokens, dApps, and Ethereum, this book will also examine the main categories that are poised for enormous opportunities. They include infrastructure, consumer apps, enterprise apps, and the metaverse. For each of these, I will have use cases of successful companies. How To Create a Web3 Startup covers the unique funding strategies, the toolsets needed, the talent required, the go-to-market approaches, and challenges faced. You will: Work with the dev stack components Examine the success factors for infrastructure, consumer, enterprise, verticals, and the Metaverse Understand the risks of Web3, like the regulatory structure and security breaches.
Chapter 1: Why Web3? -- Chapter 2: Core Technology -- Chapter 3: The Web3 Tech Stack -- Chapter 4: The Web3 Team -- Chapter 5: Decentralized Autonomous Organizations (DAOs) -- Chapter 6: NFTs, Gaming and Social Networks -- Chapter 7: DeFi -- Chapter 8: The Metaverse -- Chapter 9: Taxes and Regulations. Glossary.
Keywords: Information technology-Management.; Computer science; Entrepreneurship; New business enterprises; Venture capital; Data protection; Electronic data processing-Management.; Business IT Infrastructure; Computer Science; Entrepreneurship; Start-Ups and Venture Capital; Data and Information Security; IT Operations